Timing of Endoscopic Transmural Drainage for Pancreatic Necrosis: Expanding the Horizon! - Rana, Surinder Singh (Journal of Digestive Endoscopy, 2023)
Endoscopic transluminal drainage (ETD) has been traditionally performed on collections that have a well-formed enclosing wall and therefore it was advocated for walled-off necrosis. However, recently, retrospective studies have reported that ETD can be safely performed in patients with collections without a well-formed wall also and reported outcomes better than those patients who were treated with percutaneous drainage. The evidence for safety and efficacy of early ETD for infected pancreatic necrosis is scanty and therefore, in this news and views, I will be discussing a recently published systematic review and meta-analysis comparing outcomes after early (<4 weeks) and standard (≥4 weeks) drainage of pancreatic necrosis.
Keywords: pancreatic necrosis; stent; acute pancreatitis